An empirical study on the impact of supply chain practices on competitive position of MNEs in Malaysia - Sambasivan, Murali; Jacob, George (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
Effective supply chains provide opportunities to create sustainable competitive advantage and enhance the competitive position of companies. This paper attempts to study the impact of supply chain practices on competitive position of a company. This research surveyed senior managers in various MNEs in Malaysia. The results show that efforts in: (1) improving customer satisfaction, (2) selecting the right suppliers, (3) improving the efficiency of operations and (4) implementing the right quality practices have significant impact on the competitive position of the company.